EPCO-36. GENOMIC INSTABILITY AND TRANSCRIPTOMIC SIGNATURES UNDERLYING EPIGENETIC MENINGIOMA SUBGROUPS REVEALS MECHANISMS OF IMMUNE INFILTRATION AND THERAPEUTIC VULNERABILITIES. (9th November 2020) - Choudhury, Abrar; Magill, Stephen; Prager, Briana; Eaton, Charlotte; Lam, Tai-Chung; Pu, Jenny Kan-Suen; Li, Lai Fung; Leung, Gerald; Vasudevan, Harish N; Lucas, Calixto-Hope G; Chan, Jason W; Wendt, Jake; et al.
Abstract: BACKGROUND: Meningioma treatments are limited due to incomplete understanding of meningioma biology. To address this, we performed multiplatform molecular profiling on 565 meningiomas with comprehensive clinical data to define genomic drivers and identify therapeutic vulnerabilities. METHODS: DNA methylation profiling was performed on meningiomas from UCSF (n=200, discovery) and Hong Kong University (n=365, validation). Median follow-up was 5.6 years, and there were 388/142/35 WHO grade I/II/III meningiomas. Copy number variants (CNVs) were calculated for all meningiomas, and RNA sequencing was performed on UCSF meningiomas. Cell type deconvolution, metagenomics, CRISPR, and pharmacology were used for mechanistic and functional validation. RESULTS: Unsupervised hierarchical clustering of differentially methylated DNA probes revealed that meningiomas were comprised of 3 epigenetic subgroups associated with good, intermediate, and poor outcomes, with representation from all WHO grades in each subgroup. Meningiomas from the subgroup with the best outcomes (52% WHO grade I) were distinguished by recurrent gain of Chr5. Meningiomas from the subgroup with intermediate outcomes (31% WHO grade II) were distinguished by genomic stability, enrichment of innate immune genes, and immune infiltration in the setting of endogenous retroviral gene re-expression, a mechanism of immune recruitment. The most aggressive subgroup of meningiomas (57% WHO grade III) was distinguished by genomic instability, including recurrent loss of Chr22q harboring NF2, and decreased immune infiltration. Consistently, NF2 suppression in primary meningioma cells derived from immunogenic meningiomas decreased expression of innate immune genes critical for immune recruitment, suggesting a novel immunostimulatory function of NF2 . The most aggressive subgroup of meningiomas were further distinguished by activation of the mitogenic FOXM1 transcriptional program, and recurrent loss of Chr9p harboring CDKN2A/B, which rendered primary meningioma cells from this subgroup susceptible to CDK4/6 inhibitors. CONCLUSIONS: Meningiomas are comprised of 3 epigenetic subgroups defined by genetic mechanisms driving immune infiltration in the tumor microenvironment and meningioma cell proliferation.